Late-onset postpartum eclampsia: Do not ignore the headache! - Singh, Ranju; Saini, Surbhi; Jain, Aruna (Indian Journal of Case Reports, 2020)
Pre-eclampsia and eclampsia continue to be a poorly understood neurological entity of pregnancy that substantially contributes to maternal morbidity and mortality. The onset of postpartum eclampsia occurring more than 48 h after the onset of the postpartum period is defined as late-onset postpartum eclampsia (LPE). We report the case of a 27-year-old woman who had eclampsia on the 6th postpartum day after cesarean section with a throbbing headache as the only prodromal symptom and normal blood pressure (BP) recordings at the time of convulsion. She was managed successfully with magnesium sulfate therapy. This case emphasizes that headache and/or visual changes developing during the postpartum period can be the only warning symptom of impending eclampsia and that LPE can occur even when the BP has normalized post-delivery. Early diagnosis and subsequent initiation of appropriate therapy prevent severe complications.